Cytoreductive Nephrectomy and Nephrectomy/Complete Metastasectomy for Metastatic Renal Cancer - Paul Russo; Mark Synder; Andrew Vickers; Varuni Kondagunta; Robert Motzer (The Scientific World Journal)
The objective of this study was to determine our institutional experience with cytoreductive nephrectomy alone or in conjunction with nephrectomy complete metastasectomy. Between July 1989 and September 2003, we queried our department's renal tumor database for patients undergoing cytoreductive nephrectomy alone or in conjunction with complete metastasectomy. Clinical and pathological factors analyzed included primary tumor size, stage and histological subtype, age, gender, Karnofsky Performance Status (KPS) prior to nephrectomy, number and location of metastatic sites, and the presence or absence of any systemic therapy. Preoperative laboratory values analyzed included hemoglobin (HGB), calcium (CA), albumin (ALB), lactose dehydrogenase (LDH), alkaline phosphatase (ALP), and corrected calcium. Corrected calcium was defined as follows: corrected calcium = total calcium - 0.707*(albumin - 3.4). During this time frame, 1628 patients underwent nephrectomy (partial or radical) for renal masses, 91 (5.6%) of whom had metastatic disease. In this group, 71% of patients were male, 88% of patients had a KPS of 80% or greater, and 92% had conventional clear cell histology. Sixty-four percent of patients had a single site of metastatic disease, with lung the most common, followed by bone, adrenal, brain, and liver. Sixty-one patients (67%) had nephrectomy with removal of all metastatic sites (nephrectomy/complete metastasectomy) and 30 (33%) had cytoreductive nephrectomy alone. Median survival for patients undergoing nephrectomy/complete metastasectomy was 30 months. Median survival for patients undergoing cytoreductive nephrectomy alone was 12 months. Perioperative complications occurred in 13% of patients and four patients died within 30 days of their operation. For patients with metastatic renal cell carcinoma, surgical resection of the primary tumor alone (cytoreductive nephrectomy) or in conjunction with metastasectomy can be accomplished with acceptable perioperative morbidity and mortality. This surgical experience provides a contemporary foundation as new targeted therapeutic agents are integrated into the neoadjuvant or adjuvant treatment of locally advanced and metastatic renal cancer.